A comprehensive numerical simulation of traffic pollution in a street during one diurnal cycle. (1st January 2000) - Mestayer, Patrice G.; Sini, Jean-Francois
A numerical simulation of the traffic pollutant transport diffusion within one busy street of Nantes city centre has been realised for a real-time duration of 24 hours, with a time step of 20 ms, in low wind, sunny conditions. It has been generated with the urban canopy model CHENSI, which includes sub-models of thermal buoyancy, traffic emission rates, car induced turbulence. A number of frames of the simulation film are selected to illustrate the mechanism and the influence of the coupling between dynamic and thermal convections upon the flow regimes, the street ventilation, the distribution of the pollutant concentrations and the pollutant residence times.